2018
DOI: 10.1111/jcmm.13870
|View full text |Cite
|
Sign up to set email alerts
|

Targeting c‐met receptor tyrosine kinase by the DNA aptamer SL1 as a potential novel therapeutic option for myeloma

Abstract: Hepatocyte growth factor (HGF)/c‐met pathway activation has been implicated in the pathogenesis of multiple myeloma (MM), and blocking this pathway has been considered a rational therapeutic strategy for treating MM. Aptamers are single‐stranded nucleic acid molecules that fold into complex 3D structures and bind to a variety of targets. Recently, it was reported that DNA aptamer SL1 exhibited high specificity and affinity for c‐met and inhibited HGF/c‐met signaling in SNU‐5 cells. However, as the first c‐met‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
(74 reference statements)
2
15
0
Order By: Relevance
“…These in vitro studies were also validated by an in vivo pre-clinical model utilizing NOD/SCID mice xenotransplanted with RPMI8226.R5 cells [35] . Altogether these observations are in agreement with data presented in two other manuscripts describing increased sensitivity to bortezomib and doxorubicin of the c-MET siRNA-silenced U266 cell line [42,43] . These findings suggest that c-MET overactivation and higher p-c-MET levels could represent a marker of multidrug resistance in MM.…”
Section: Inhibitor Of C-met Tyrosine Kinasesupporting
confidence: 92%
See 1 more Smart Citation
“…These in vitro studies were also validated by an in vivo pre-clinical model utilizing NOD/SCID mice xenotransplanted with RPMI8226.R5 cells [35] . Altogether these observations are in agreement with data presented in two other manuscripts describing increased sensitivity to bortezomib and doxorubicin of the c-MET siRNA-silenced U266 cell line [42,43] . These findings suggest that c-MET overactivation and higher p-c-MET levels could represent a marker of multidrug resistance in MM.…”
Section: Inhibitor Of C-met Tyrosine Kinasesupporting
confidence: 92%
“…A confirmation of the involvement of c-MET in disease progression was recently provided by Zhang et al [ 44 ] , through the determination of the prevalence of c-MET overexpression in a publicly available gene expression profiling database of myeloma: c-MET resulted in being significantly higher in MGUS ( n = 44) vs. healthy controls ( n = 22), and even significantly much higher in a large cohort of newly diagnosed MM cases ( n = 599), in association with poor outcomes [ 44 ] . By the use of a new DNA aptamer (SL1), selectively targeting c-MET with high affinity [ 45 ] , Zhang et al [ 44 ] further demonstrated inhibition of growth, adhesion, and migration of malignant plasma cells co-cultured with the stromal HS5 cell line and synergistic effects when used in combination with bortezomib.…”
Section: Therapeutic Approaches Targeting Hgf/c-met Axis To Overcome ...mentioning
confidence: 63%
“…Aptamers not only can detect previously known tumor markers but also can be utilized for discovery of potential novel biomarkers in human cancers 15 . Many aptamers have been used to detect a variety of cancers by targeting tumor markers, such as nucleolin, 16 tenascin, 17 PTK7, 18 MUC1, 19 c-Met, 20 and matrix metalloprotease-9 (MMP-9) 21 . Therefore, generating a group of aptamers with high specificity is an effective and realistic method to discover novel tumor biomarkers and to construct a targeted delivery system 15 …”
Section: Introductionmentioning
confidence: 99%
“…Given the impressive independent single‐agent activity of MK1775 against myeloma, we next aimed to verify whether this compound could be combined with conventional anti‐MM drugs to create new treatment regimens. Since the myelosuppressive effect of bortezomib (BTZ) is typically mild, transient and non‐cumulative, BTZ‐based combinations are well‐liked in preclinical studies that set the framework for clinical application 33 . Hence, combinations of various concentrations of MK1775 and BTZ were first tested in vitro , and calculations of combination index (CI) values using CalcuSyn software indicated synergistic effects between MK1775 and BTZ (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%